A visão dos exploradores: uma análise sociológica sobre a exploração do trabalho infantil no complexo Beira Rio em Macapá - (:unkn) unknown (UNIFAP – Universidade Federal do Amapá, 2013)
This research is an account of the process of exploitation of child workers in the Riverside Complex (Complexo Beira Rio), located in the shopping center of the city of Macapa. We initially focus on the major theorists of sociology to explain the concept of work, then was made a historical overview of child labor in Brazil, from the colonial period to the present and an outline of the legal rights guaranteed under Brazilian law the child. In order to define the problem, a survey was conducted with the objective of analyzing the reasons which lead the child to labor early. Finally, we analyze the performance of key projects and institutions for the protection of children and adolescents. Although there are laws prohibiting this practice and should protect it, this does not occur due to lack of activeness on the part of the inspectors plus the ineffectiveness of public policies to eradicate this anomaly.
Keywords: Trabalho infantil; Exploração infantil; Crianças; CNPQ::CIENCIAS SOCIAIS APLICADAS